2007
DOI: 10.1186/bcr1650
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of maternal embryonic leucine zipper kinase (MELK) in mammary carcinogenesis through interaction with Bcl-G, a pro-apoptotic member of the Bcl-2 family

Abstract: Introduction Cancer therapies directed at specific molecular targets in signaling pathways of cancer cells, such as tamoxifen, aromatase inhibitors and trastuzumab, have proven useful for treatment of advanced breast cancers. However, increased risk of endometrial cancer with long-term tamoxifen administration and of bone fracture due to osteoporosis in postmenopausal women undergoing aromatase inhibitor therapy are recognized side effects. These side effects as well as drug resistance make it necessary to sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 155 publications
(94 citation statements)
references
References 17 publications
2
92
0
Order By: Relevance
“…Previous studies have identified some MELK substrates, including ASK1, ZNF622, BCL2L14, and CDC25B (Davezac et al, 2002; Jung et al, 2008; Lin et al, 2007; Seong et al, 2002). The apoptotic functions of MELK are mediated by ASK1 and BCL2L14 regulation (Jung et al, 2008; Lin et al, 2007), while its cell cycle regulatory effects are proposed to be mediated by its phosphorylation of CDC25B (Davezac et al, 2002; Mirey et al, 2005). In addition to regulating apoptosis and cell cycle, MELK also regulates other aspects of cell biology.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified some MELK substrates, including ASK1, ZNF622, BCL2L14, and CDC25B (Davezac et al, 2002; Jung et al, 2008; Lin et al, 2007; Seong et al, 2002). The apoptotic functions of MELK are mediated by ASK1 and BCL2L14 regulation (Jung et al, 2008; Lin et al, 2007), while its cell cycle regulatory effects are proposed to be mediated by its phosphorylation of CDC25B (Davezac et al, 2002; Mirey et al, 2005). In addition to regulating apoptosis and cell cycle, MELK also regulates other aspects of cell biology.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 MELK is activated by autophosphorylation, and once it is activated, it then phosphorylates several substrates, such as a pro-apoptotic molecule Bcl-G and a cell cycle protein CDC25. 1,5 In addition, we and others have reported that MELK induces expression of oct3/4, a well-known a stem cell marker. 6,7 However, the detailed downstream signaling pathway of MELK in cancer cells is still not fully understood.…”
mentioning
confidence: 80%
“…MELK is also over-expressed in most types of solid tumors, including breast, colon, liver, lung, melanoma, and ovarian cancer (Gray et al, 2005). Furthermore, many publications have reported that knocking down MELK using RNAi inhibited the proliferation of cell lines derived from these cancer types (Gray et al, 2005; Lin et al, 2007; Kuner et al, 2013; Du et al, 2014; Kig et al, 2013; Speers et al, 2016; Alachkar et al, 2014; Marie et al, 2008; Nakano et al, 2008; Hebbard et al., 2010; Wang et al, 2014; Choi et al, 2011; Xia et al, 2016; Gu et al, 2013). In particular, MELK has been identified as a key driver of basal-type breast cancer, suggesting a novel therapeutic approach to treat this disease (Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%